PSYCHOPRAGMATIC ANALYSIS OF SPEECH ACT OF THE PERPETRATORS OF THE VIOLENCE TOWARD MINANGKABAU WOMEN (ANALISIS PSIKOPRAGMATIK TINDAK TUTUR PELAKU KEKERASAN TERHADAP PEREMPUAN MINANGKABAU) - Revita, Ike; Trioclarise, Rovika; Anggreiny, Nila (Universitas PGRI Sumatera Barat, 2019)
Minangkabau is identical with matrilineal system. Women are at the respected position in society. However, many Minangkabau women become the victims of violence. These Minangkabau women are verbally violated. These verbal violences are categorized as an action called speech act. This writing then tries to describe the speech acts of the perpetrators of the violence toward Minangkabau women. The aim of the research is to identify the types of speech act of the perpetrators of violence toward Minangkabau women from psychopragmatic perspective. The research was conducted in Padang city. The data were are collected by having interview, focus group discussion, and observation toward around 10 women, 2 community leaders, and 20 society members. The analysis was done by relating it to the concept of speech act by Austin (1962), Revita (2014), and Searle (1969). The result of analysis is descriptively presented. The data indicated that there are four types of speech acts used by the perpetrators of the violence toward Minangkabau women. They are 1) declaration; 2) expressive; 3) comissive; and 4) directive